2019
DOI: 10.1021/acs.nanolett.9b01057
|View full text |Cite
|
Sign up to set email alerts
|

Small Alkaline-Earth-based Core/Shell Nanoparticles for Efficient Upconversion

Abstract: The optical efficiency of lanthanide-based upconversion is intricately related to the crystalline host lattice. Different crystal fields interacting with the electron clouds of the lanthanides can significantly affect transition probabilities between the energy levels. Here, we investigate six distinct alkaline-earth rare-earth fluoride host materials (M1-xLnxF2+x, MLnF) for infrared-to-visible upconversion, focusing on nanoparticles of CaYF, CaLuF, SrYF, SrLuF, BaYF, and BaLuF doped with Yb3+ and Er3+. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…Different from these two approaches, doping non-Ln ions to enhance the luminescence through modulating the local chemical environment of the emitting centers doesn't necessarily increase the particle size apart from forming more stable structures (Huang et al, 2019 ). Because of the interplay between the 4f electrons of Er 3+ and the crystal field of the host doped with non-Ln ions, the probability of radiative transitions within Er 3+ can hopefully be enhanced by relaxing the selection rules (Fischer et al, 2019 ). For example, metal ions such as Li + , Ca 2+ , Mn 2+ , and Fe 3+ , were adopted as non-Ln dopants to enhance the up-conversion luminescence (Cheng et al, 2012 ; Zeng et al, 2014 ; Tang et al, 2020b ; Verma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from these two approaches, doping non-Ln ions to enhance the luminescence through modulating the local chemical environment of the emitting centers doesn't necessarily increase the particle size apart from forming more stable structures (Huang et al, 2019 ). Because of the interplay between the 4f electrons of Er 3+ and the crystal field of the host doped with non-Ln ions, the probability of radiative transitions within Er 3+ can hopefully be enhanced by relaxing the selection rules (Fischer et al, 2019 ). For example, metal ions such as Li + , Ca 2+ , Mn 2+ , and Fe 3+ , were adopted as non-Ln dopants to enhance the up-conversion luminescence (Cheng et al, 2012 ; Zeng et al, 2014 ; Tang et al, 2020b ; Verma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite huge progress in the synthesis and understanding of the properties of UCNPs during recent years 26,27 , a number of limitations still have to be solved before these unique particles are translated into clinical praxis. One of the main challenges is their poor colloidal stability in water, and more importantly, in physiological buffers (e.g., PBS).…”
mentioning
confidence: 99%
“…[46] We use Lu 3+ as the rare-earth component of the host materials based on previous studies that have shown higher upconversion efficiencies for MLuF UCNPs. [46,50] Efficient blue upconversion in the b-NaLnF 4 system is generally achieved with 20 %Y b 3+ and % 0.5 %T m 3+ . [51] Based on the average distance between active ions in our alkaline earth host lattices,wedope the MLnF UCNPs with 28 %Yb 3+ and 0.5 %T m 3+ (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[44,45] We also demonstrated the potential of alkaline-earth rare-earth fluoride (M 1Àx Ln x F 2+x, MLnF) host lattices for small (sub-20 nm) lanthanide-based NIR to visible Yb 3+ -Er 3+ upconversion. [46] Theh igh UCQY of these particles encouraged us to consider this new alkaline-earth host for UV and visible emission with Yb 3+ -Tm 3+ upconversion.…”
Section: Introductionmentioning
confidence: 99%